CONTESTATION AND REPRESENTATION: New Forms of Religious Authority in Disruptive Indonesia - Jahroni, Jajang; Faisal Bakti, Andi M. (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2022)
This article seeks to elaborate the roles of some Muslim scholars and activists who, thanks to the advancement of internet technology, have shaped new forms of religious life in Indonesia. Using social media platforms such as YouTube, Instagram, Facebook, and Twitter, they advocate their ideas and attract followers from Muslim groups. These Muslims are divided into four ideologies, namely conservative, moderate, liberal and traditionalist. As this article argues, thanks to their online activism, they successfully shape a new religious authority replacing the old model. Nevertheless, as this article also suggests, religious activism on online media outlets does not lead to the pluralism of religious views and understandings. In contrast, this activism creates the so called echo chamber or isolated bubbles, which means that the activists’ voices are only observed by their limited followers. Taking the activism of most popular conservative activists Felix Siauw, it sees that his view reverberates only among his social media followers and fails to attract those who embrace other views orideologies. The followers of the moderate, the liberal, and the traditionalist on the other hand tend to be heterogenous creating a noisy minority. This leads to the vibrant and robust religious discourses.